Creative Review of Amelia Walker's Alogopoiesis - Rhodes, Kendrea (Art/Research International, 2024)
This review of Amelia Walker’s Alogopoiesis is an interdisciplinary response, reflecting Walker’s own creative approach of employing both form and content. Creative nonfiction, critical thinking, and a mixed media artwork response to Alogopoiesis reflect the effects that reading it has had on me as a creative, as a researcher, and as a living being. It is a happy coincidence that I chose to open the book in a café on Mount Myoko in Japan, and, as I climbed through the pages, I discovered a multitude of connections to my many worlds. I began walking beside each protagonist, nodding, feeling, staying. The word alogopoiesis, made up from alogia and poiesis, is an apt portmanteau for this body of work. Alogopoiesis renders an unsilencing. A slow-rebuild, remaking, and sensing of gaps where the unspoken reside. This book sharpened my outlook. My in-look. Replacing my rose-coloured glasses with recognition as I sank into stories of mental distress, violence, abuse, heartbreak, and prejudice.